2016
DOI: 10.1002/2015gl067388
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced terrestrial carbon preservation promoted by reactive iron in deltaic sediments

Abstract: We examined the role of reactive iron (FeR) in preserving organic carbon (OC) across a subaerial chronosequence of the Wax Lake Delta, a prograding delta within the Mississippi River Delta complex. We found that ~15.0% of the OC was bound to FeR, and the dominant binding mechanisms varied from adsorption in the youngest subaerial region to coprecipitation at the older, vegetated sites. The δ13C of the iron‐associated OC was more negative than the total OC (mean = −2.6‰), indicating greater preference for terre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
86
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 57 publications
9
86
0
Order By: Relevance
“…After 27 months of WTD treatment, extracellular enzyme activity, SOC and lignin phenols are examined together with different Fe species in the air-exposed (0–20 cm) relative to the submerged (30–40 cm) soil layers. In particular, similar to Shields et al 34,. we use dithionite to remove crystalline and amorphous Fe oxides25 that may associate with SOC and quantify Fe-bound lignin phenols that are subsequently exposed and amenable to CuO oxidation.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…After 27 months of WTD treatment, extracellular enzyme activity, SOC and lignin phenols are examined together with different Fe species in the air-exposed (0–20 cm) relative to the submerged (30–40 cm) soil layers. In particular, similar to Shields et al 34,. we use dithionite to remove crystalline and amorphous Fe oxides25 that may associate with SOC and quantify Fe-bound lignin phenols that are subsequently exposed and amenable to CuO oxidation.…”
supporting
confidence: 76%
“…Therefore, an improved method is needed to quantify Fe-bound lignin phenols in the soil matrix. Recently, Shields et al 34. observed altered yields of lignin phenols upon CuO oxidation after removing reactive Fe with dithionite from Mississippi delta sediments due to the release of Fe-bound lignin.…”
mentioning
confidence: 99%
“…The higher sedimentary sand fractions (~85%) at sites such as L1 and L2 in the river channel have reduced the amount of clay particles (average CF ~3%) and associated negative charges, which could hindered the formation of aggregates and enabled the decomposition of terrestrial C org (enriched in δ 13 C values). Moreover, recent work has shown that approximately 15.0%–(21.5 ± 8.6)% of the C org in marine sediments is directly bound to reactive terrestrial‐derived Fe through the chelation or coprecipitation (Lalonde et al, ; Shields et al, ). Coarse particles in the river channel sediments tend to have low fractions of highly reactive iron (indicated by low contents of Fe; Figure ), suggesting that these sites likely contain the low proportions of reactive Fe‐associated C org compared to the estuarine sites.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive Fe minerals, such as oxides, sulfides, phosphates and carbonates, are involved in diagenetic reactions in sediments and consequently influence the cycling of carbon and nutrients (e.g., Berner, 1970;Slomp et al, 1996a,b;Lovley et al, 2004;Jilbert and Slomp, 2013;Kraal et al, 2015;Robertson et al, 2016). Iron has also recently been shown to stabilize organic carbon in sediments, promoting carbon 5 burial (Lalonde et al, 2012;Shields et al, 2016). Hence, the lateral and vertical distribution of Fe in sediments is important for broader biogeochemical cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Fe has recently been suggested to play an important role in carbon burial (Lalonde et al, 2012;Shields et al, 2016) and nitrogen cycling (Robertson et al, 2016) in marine sediments. 15…”
Section: Introductionmentioning
confidence: 99%